TRPV1 inhibits the ventilatory response to hypoxia in adult rats, but not the CO 2 -drive to breathe - Patrone, Luis Gustavo A. [UNESP]; Duarte, Jaime B. [UNESP]; Bícego, Kênia Cardoso [UNESP]; Steiner, Alexandre A.; Romanovsky, Andrej A.; Gargaglioni, Luciane H. [UNESP] (MDPI, 2019)
Receptors of the transient receptor potential (TRP) channels superfamily are expressed in many tissues and have different physiological functions. However, there are few studies investigating the role of these channels in cardiorespiratory control in mammals. We assessed the role of central and peripheral TRPV1 receptors in the cardiorespiratory responses to hypoxia (10% O 2 ) and hypercapnia (7% CO 2 ) by measuring pulmonary ventilation ( ˙V E ), heart rate (HR), mean arterial pressure (MAP) and body temperature (Tb) of male Wistar rats before and after intraperitoneal (AMG9810 [2.85 µg/kg, 1 mL/kg]) or intracebroventricular (AMG9810 [2.85 µg/kg, 1 µL] or AMG7905 [28.5 µg/kg, 1 µL]) injections of TRPV1 antagonists. Central or peripheral injection of TRPV1 antagonists did not change cardiorespiratory parameters or Tb during room air and hypercapnic conditions. However, the hypoxic ventilatory response was exaggerated by both central and peripheral injection of AMG9810. In addition, the peripheral antagonist blunted the drop in Tb induced by hypoxia. Therefore, the current data provide evidence that TRPV1 channels exert an inhibitory modulation on the hypoxic drive to breathe and stimulate the Tb reduction during hypoxia.
Keywords: Blood pressure; Channels; Chemosensitivity; Hypercapnia; Hypothermia; Ventilation